Le monnayage argien d’époque romaine - Flament, Christophe, 19??- (Paris : Athènes)
135 sayfa, 14 sayfa resim
Keywords: “Due to its longevity and to the great variety of types that adorn the different issues, the Argive monetary corpus is undoubtedly one of the most interesting of Imperial Greece. It is composed by two asymmetrical groups, each corresponding to a distinct period: the first one, stretching from Hadrian to Marcus Aurelius, opens up new possibilities for the interpretation of Pausanias; the other, strarting mainly under the reign of Septimius Severus, saw a deterioration of the initial program and a steady reduction in the number of images, while the uninterrupted production of coins until the reign of Gallienus provides a major landmark for the history of the 3rd century devaluations. A confrontation with other Peloponnesian mints allows us also to determine the few mints that were still active at the time and to considerably relativize the extent of iconographic variation between cities, as can be evidenced by a systematic comparison of the images showing the Palaemonium in Corinth and the Nymphaeum in Argos.” --